A multicentric analysis of prognostic factors in malignant pleural mesothelioma - Batista, Mafalda (2024)
Background: Malignant pleural mesothelioma is a rare entity with poor prognosis, linked to previous asbestos exposure. The main goal of this study was to analyse the impact of clinical factors on mesothelioma prognosis. Methods: Retrospective cohort study of patients with malignant pleural mesothelioma in three Portuguese institutions, from 1999 to 2020. Statistical analysis was performed with Kaplan–Meier method and Cox regression using IBM SPSS® v25. Results: 60 patients were included, with male predominance (70%) and a median age of 69 years old. At diagnosis, 61% had advanced TNM stage (TNM III-IV) and 18% had an ECOG-PS ≥ 2. Asbestos exposure was stated in 48%. Epithelioid mesothelioma was the most prevalent histological subtype (81%). The majority received first line chemotherapy, in 10% combined with surgery, and two patients received immunotherapy after progression. Median overall survival (OS) was 13 months and median progression free survival was 10 months. A lower OS was observed in patients with ECOG-PS ≥ 2, age ≥ 70 years, TNM stage III-IV, anaemia, and hypoalbuminemia. Applying the decision tree model proposed by Brims et al. in our population, a significant difference in median OS was observed between the risk groups. In a multivariate analysis using Cox regression, Brims risk group 4, older age and advanced TNM stage were identified as independent negative prognostic factors. Conclusion: Recognition of these prognostic factors at diagnosis and use of specific prognostic models can help guide malignant pleural mesothelioma management.